Рассказы о животных - Черноглазов Владимир Юрьевич (Школьная библиотека, 2010)
Экземпляры: ФО-6 (20110525) / Инвентарный номер: 47038 / Цена: 104.50 / Сис.шифр: Р2 ср. / Авт.знак: Р 24 / ГРНТИ: 17.82.93 / ББК: 84(2Рос.Рус)6